2004
DOI: 10.1161/01.str.0000147039.49252.2f
|View full text |Cite
|
Sign up to set email alerts
|

Anteromedian, Central, and Posterolateral Infarcts of the Thalamus

Abstract: Background and Purpose-Thalamic infarcts have traditionally been classified into 4 territories: anterior, paramedian, inferolateral, and posterior. The purpose of this study was to review this classical versus variant distribution in patients with thalamic stroke. Methods-We reviewed all patients with a first clinical stroke included in the Lausanne Stroke Registry between 1990 and 2002. Among 71 patients with an acute stroke isolated to the thalamus confirmed by MRI, we selected all patients with lesions outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 42 publications
8
125
5
6
Order By: Relevance
“…Arterial strokes will follow arterial distributions, while neoplasms are more inclined to circumscribe tissue planes. 2,4,11,15,27,45,58,70 Deep AVFs and deep venous thromboses produce T2/FLAIR hyperintensities centered within the bilateral anteromedial thalamic regions, though extensions beyond the thalami are reported in a significant number of cases. 5,18,21,22,76,77 In many instances, a definitive diagnosis for the thalamic dementia syndrome cannot be reached after history, physical examination, and MRI.…”
Section: Thalamic Dementia Syndrome: Differential Diagnosis and Workupmentioning
confidence: 99%
“…Arterial strokes will follow arterial distributions, while neoplasms are more inclined to circumscribe tissue planes. 2,4,11,15,27,45,58,70 Deep AVFs and deep venous thromboses produce T2/FLAIR hyperintensities centered within the bilateral anteromedial thalamic regions, though extensions beyond the thalami are reported in a significant number of cases. 5,18,21,22,76,77 In many instances, a definitive diagnosis for the thalamic dementia syndrome cannot be reached after history, physical examination, and MRI.…”
Section: Thalamic Dementia Syndrome: Differential Diagnosis and Workupmentioning
confidence: 99%
“…Comparisons of when thalamic strokes do and do not induce amnesia have consistently found that damage to this tract is the best predictor of memory loss (Von Cramon et al 1985;Ghika-Schmid and Bogousslavsky 2000;Van der Werf et al 2000, 2003bCarrera et al 2004). One of these studies also linked recognition deficits to mammillothalamic tract damage ( Van der Werf et al 2003b).…”
Section: The Anterior Thalamic Nucleimentioning
confidence: 99%
“…A second patient was described with memory problems associated with pathology in the caudal intralaminar nuclei (e.g., including the center median nucleus and the parafascicular nucleus), but these problems appeared to be due to a loss of attention and increased distractibility (Mennemeier et al 1992). Problems with arousal and levels of awareness have since been further linked with damage to the intralaminar nuclei (Van der Werf et al 2002;Carrera et al 2004) but again could reflect disconnections due to white matter damage.…”
Section: Intralaminar and Midline Thalamic Nucleimentioning
confidence: 99%
“…The vascular territory of the lesion suggests a cardiac source of embolism. [2][3][4] Lipomas are benign nonmyxomatous neoplasms of the heart that normally cause no symptoms and their diagnosis is often accidental. [5][6][7] They represent 10% of the overall cardiac tumor masses arising from cardiac tissue and they are most frequently located in the right atrium.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…2,3 Its etiological relationship with stroke is not well established. We describe the case of a thalamic stroke probably caused by paradoxical embolism from a right atrial lipoma through a patent foramen ovale.…”
mentioning
confidence: 99%